2018
DOI: 10.1515/ijamh-2017-0138
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress and growth among CPR survivors in the southeast of Iran

Abstract: Background Almost 7.2%-10.6% of patients survive CPR in Iran. Most of them experience post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG). There are limited studies to assessing the correlation between these two psychological outcomes among CPR survivors. Objective This study aimed to examine the correlation between PTSD and PTG among CPR survivors in South-East Iran. Subjects Using Quota sampling, 163 CPR survivors in two provinces in the South-East of Iran were selected to participate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The high level of healthcare team contact with the injured and patients makes them anxious (2). Some people talk about death, but there are also many people who avoid it and experience death anxiety (3). Death anxiety is a multidimensional concept with emotional, cognitive, and empirical characteristics and it is inversely related to the culture (4).…”
Section: Introductionmentioning
confidence: 99%
“…The high level of healthcare team contact with the injured and patients makes them anxious (2). Some people talk about death, but there are also many people who avoid it and experience death anxiety (3). Death anxiety is a multidimensional concept with emotional, cognitive, and empirical characteristics and it is inversely related to the culture (4).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Iranmanesh et al, the scale reliability coefficient was 0.87 [33] . In addition, Seyed Bagheri et al have used this scale in their study and mentioned its reliability coefficient as 0.83 [34] . In the study of Creamer et al, the IES-R demonstrated high internal consistency (Cronbach's alpha=0.96) and about subscales intrusion: 0.94; avoidance: 0.87; hyperarousal: 0.91 was reported [35] .…”
Section: Methodsmentioning
confidence: 99%
“…In the IES-R scale, the total score ranges from 0 -23 (normal), 24 -32 (a low psychological impact), 33 -36 (a medium psychological impact), to > 37 (a severe psychological impact). In Iran, the Cronbach's alpha coefficient of the total scale was 0.83 (27). The DASS-21 and IES-R were previously used in studies related to COVID-19 outbreak (28,29).…”
Section: Research Toolsmentioning
confidence: 99%